Fundamental study on functionality of synthetic sulfides: Evaluation of metal sulfides as solid lubricant - Shuhei Ishikawa; Tomohiro Sato; Ken-ichi Saitoh; Masanori Takuma; Yoshimasa Takahashi (Jurnal Tribologi, 2019)
Replacement of exhaustible and harmful resources used as solid lubricants is required for sliding elements such as plain bearings. In particular, the substitution of lead containing in the lead bronze is considered an urgent task. Therefore, in this study, attention was focused on metal sulfides (Cu2S, Cu5FeS4, SnS, TiS2, etc) as a substitute material for lead. After synthesis of sulfide and preparation of sintered body, friction and abrasion test was carried out and applicability as solid lubricant was investigated. The tribological properties of the dry conditions were evaluated by a journal type high speed tester. As a result, the friction coefficient of the bronze specimen without sulfide was about 0.3, whereas the bronze specimen containing sulfide showed a friction coefficient of about 0.1, indicating that the sulfide reduced the frictional resistance. Among them, the specimens containing Cu2S and Cu5FeS4 exhibited a lower friction coefficient. It is considered that this is influenced not only by the effect of hardness but also by film formation by sulfide.